Development of An Instructional Design Model for Blended Coaching and Action Learning for Supervisors to Enhance Secondary School Teachers’ ICT Utilization - Jitwiriya, Kallayanee; Thangkabutra, Theeravadee; Natakuatoong, Onjaree (Scholar: Human Sciences, 2018)
Supervisors are responsible for guiding teaching and learning management and exchanging academic learning with teachers and school administrator in order to enhance ICT utilization among secondary school teachers. Applied guiding process had been allowing supervisors to meet and discuss with teachers in the school. Further to the advancement of ICT technology nowadays, supervisors are able to provide guidance through blended coaching in order to enhance secondary school teaching and apply action learning principle for better ability of secondary school teachers in utilizing ICT. This research aimed to develop a blended coaching and action learning of supervisors to enhance secondary school teachers’ ICT utilization. Researchers had applied research process and developed a model and tested with sample group including a supervisor and 18 secondary school teachers for a month.